Are you on the right track? The effect of educational tracks on student achievement in upper-secondary education in Hungary - Zoltán Hermann (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
The paper attempts to identify causal effects of being enrolled in different educational tracks on student achievement in upper-secondary education in Hungary. Rejected and admitted students are compared who applied to the same school and performed similarly in the previous grade. Average treatment effects on the treated are estimated with a matching method. Results indicate that higher track significantly raises student achievement. Beside the effect of tracks, the schools preferred by students within the tracks also provide better educational quality. Comparing the effects of tracks and differences within the tracks reveals that the advantage of the academic track does not differ from that of better schools in general. At the same time, the vocational track incurs substantial losses that are in part specific to that track.
Keywords: I20; I21; I24; 330; education; tracking; matching; equality of opportunity